2017
DOI: 10.3171/2016.8.spine16318
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord herniation repair with microstaples: case report

Abstract: Idiopathic spinal cord herniation (ISCH) is a relatively rare and frequently misdiagnosed condition. It preferentially affects women and causes progressive thoracic myelopathy that presents as a Brown-Séquard syndrome or as spastic paraparesis. Although its etiology and pathogenesis are controversial, ISCH is characterized by the presence of an anterior dural defect that allows the incarceration of a segment of the cord. Typically, a C-shaped ventral displacement and kinking of the cord are visible on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…We reviewed cases of BSS caused by thoracic vertebral pathologies and their treatments reported from 1978 to 2021 14 44 ( Table 1 ). Among these 50 cases, the age at presentation ranged from 11 to 76 years (average, 45.9 years).…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed cases of BSS caused by thoracic vertebral pathologies and their treatments reported from 1978 to 2021 14 44 ( Table 1 ). Among these 50 cases, the age at presentation ranged from 11 to 76 years (average, 45.9 years).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, duraplasty minimizes the risk of inadvertent spinal cord manipulation and the related postoperative neurological dysfunction, but introduces a foreign material into the patient. [ 4 , 10 , 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…It involves anterior or anterolateral displacement of spinal cord tissue through a small, ventral dural defect most typically arising in the upper/mid thoracic spine between the T2-T8 levels. [ 4 , 12 ] There are fewer than 200 such cases described in the literature. As the diagnosis of ISCH is often delayed, many patients undergo progressive irreversible neurological deterioration before diagnostic studies confirming the diagnosis and before definitive appropriate surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Watanabe et al [39] used curved scissors to widen the dural defect and observed no recurrence during follow-up. Delgado-López et al [50] found that excessive tension between defect edges could lead to suture loosening, necessitating the innovative use of special vascular clips to complete this procedure. Furthermore, Kasliwal et al [51] used the paramedian approach of laminectomy and unilateral pedicle resection for the rst time in a patient with a spinal cord herniation.…”
Section: Nakamura Et Al [26]mentioning
confidence: 99%